Human Resource Management Practices and Entrepreneurship Performance in the Agricultural Sector: Indonesia Study - Dana Budiman; Yusuf Iskandar; Ana Yuliana Jasuni (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2023)
Entrepreneurship is driving growth in Indonesia's agricultural sector, but the link between it and Human Resource Management (HRM) practices is largely unknown. A quantitative study aims to investigate this relationship. This research surveyed 355 agricultural companies in different areas and sub-sectors using a questionnaire designed for cross-sectional research. on their HR practices and entrepreneurial performance. Using Smart-PLS 4, a strong correlation between HRM strategies and entrepreneurial behavior and performance founded. HRM practices like hiring qualified staff, providing training, fair compensation, and promoting engagement can encourage entrepreneurial behavior among employees, leading to better agricultural enterprise performance. Prioritizing HRM strategies that support an entrepreneurial culture can increase productivity, promote sustainability, and motivate the workforce to tackle industry challenges.